An Unusual Case of Constitutional Mismatch Repair Deficiency Syndrome With Anaplastic Ganglioglioma, Colonic Adenocarcinoma, Osteosarcoma, Acute Myeloid Leukemia, and Signs of Neurofibromatosis Type 1: Case Report. Issue 1 (4th April 2015) - Daou, Badih; Zanello, Marc; Varlet, Pascale; Brugieres, Laurence; Jabbour, Pascal; Caron, Olivier; Lavoine, Noémie; Dhermain, Frederic; Willekens, Christophe; Beuvon, Frederic; Malka, David; Lechapt-Zalcmann, Emmanuèle; et al.
Abstract: BACKGROUND AND IMPORTANCE: Constitutional mismatch repair deficiency (CMMRD) syndrome is a disorder with recessive inheritance caused by biallelic mismatch repair gene mutations, in which mismatch repair defects are inherited from both parents. This syndrome is associated with multiple cancers occurring in childhood. The most common tumors observed with CMMRD include brain tumors, digestive tract tumors, and hematological malignancies. The aim of this study was to report new phenotypic expressions of CMMRD syndrome and add new insight to the existing knowledge about this disease. A review of the literature was conducted and recommendation for surveillance and follow-up in patients with CMMRD are proposed. CLINICAL PRESENTATION: We report for the first time in the literature, the case of a 22-year-old female patient who was diagnosed with CMMRD syndrome, with the development of 2 unusual tumors: an anaplastic ganglioglioma and an osteosarcoma. She presented initially with an anaplastic ganglioglioma and later developed several malignancies including colonic adenocarcinoma, osteosarcoma, and acute myeloid leukemia. The patient had an atypical course of her disease with development of the initial malignancy at an older age and a remarkably long survival period despite developing aggressive tumors. CONCLUSION: Many aspects of this disease are still unknown. We identified a case of CMMRD in a patient presenting with an anaplastic ganglioglioma, who underwent successful surgical resection, chemotherapy, and radiotherapy and has had one of the longest survival periods known with this disease. This case broadens the tumor spectrum observed with CMMRD syndrome with anaplastic ganglioglioma and osteosarcoma as new phenotypic expressions of this genetic defect.